Integrating digital interventions with clinical practice in youth mental health services. (June 2023) - Cross, Shane P; Nicholas, Jennifer; Bell, Imogen H; Mangelsdorf, Shaminka; Valentine, Lee; Thompson, Andrew; Gleeson, John F; Alvarez-Jimenez, Mario
Objective: Integrating digital technologies with clinical practice promises to improve access and enhance care in the context of high service demand and constrained capacity. Method: We outline the emerging research in the integration of digital tools in clinical care, known as blended care, and provide case examples of mental health technology platforms currently in use, summarise findings regarding novel technologies such as virtual reality, and outline real-world implementation challenges and potential solutions. Results: Recent evidence shows that blended care approaches are clinically effective and improve service efficiency. Youth-specific technologies such as moderated online social therapy (MOST) are achieving a range of positive clinical and functional outcomes, while emerging technologies like virtual reality have strong evidence in anxiety disorder, and accumulating evidence in psychotic conditions. Implementation science frameworks show promise in helping overcome the common challenges faced in real-world adoption and ongoing use. Conclusion: The integrated, blended use of digital mental health technologies with face-to-face clinical care has the potential to improve care quality for young people while helping overcome the growing challenges faced by youth mental health service providers.